Sport massage on sports performance - Adi S; Hilmy Aliriad; Wahyu Arbanisa; Ahmad Winoto (PHEDHERAL, 2023)
This article discusses related to sports massage to sports performance. Sport massage has good benefits and can help when finished in carrying out daily activities. This article aims to determine the effectiveness of sport massage on sports performance. The method in this article uses the literature review method in the form of data collection through trusted scientific information sources from Scholar, Scimago JR, and Science Direct with a range of data from 2015 to 2022 as well as data from the experience of researchers. In this article, states that sports massage can not only be done on athletes but can be done on the general public. Sport massage can be done on the body that feels sore after doing strenuous activities. The results show that sports massage on sports performance gets positive results where it can be a means of treatment or health maintenance. In conclusion, sports massage can help improve sports performance because it can facilitate blood circulation, reduce lactic acid levels, and relax tense muscle tissue.